Sex Differences in Subclinical Atherosclerosis and Systemic Immune Activation/Inflammation Among People With Human Immunodeficiency Virus in the United States. (14th September 2022) - Zanni, Markella V; Foldyna, Borek; McCallum, Sara; Burdo, Tricia H; Looby, Sara E; Fitch, Kathleen V; Fulda, Evelynne S; Autissier, Patrick; Bloomfield, Gerald S; Malvestutto, Carlos D; Fichtenbaum, Carl J; Overton, Edgar T; et al.
Abstract: Background: Among people with HIV (PWH), sex differences in presentations of atherosclerotic cardiovascular disease (ASCVD) may be influenced by differences in coronary plaque parameters, immune/inflammatory biomarkers, or relationships therein. Methods: REPRIEVE, a primary ASCVD prevention trial, enrolled antiretroviral therapy (ART)–treated PWH. At entry, a subset of US participants underwent coronary computed tomography angiography (CTA) and immune phenotyping (n = 755 CTA; n = 725 CTA + immune). We characterized sex differences in coronary plaque and immune/inflammatory biomarkers and compared immune-plaque relationships by sex. Unless noted otherwise, analyses adjust for ASCVD risk score. Results: The primary analysis cohort included 631 males and 124 females. ASCVD risk was higher among males (median: 4.9% vs 2.1%), while obesity rates were higher among females (48% vs 21%). Prevalence of any plaque and of plaque with either ≥1 visible noncalcified portion or vulnerable features (NC/V-P) was lower among females overall and controlling for relevant risk factors (RR [95% CI] for any plaque: .67 [.50, .92]; RR for NC/V-P: .71 [.51, 1.00] [adjusted for ASCVD risk score and body mass index]). Females showed higher levels of IL-6, hs-CRP, and D-dimer and lower levels of Lp-PLA2 ( P < .001 for all). Higher levels of Lp-PLA2, MCP-1, and oxLDL were associated with higher plaque ( P < .02) and NC/V-P prevalence, with no differences by sex. Among females but not males, D-dimer was associated with higher prevalence of NC/V-P (interaction P = .055). Conclusions: Among US PWH, females had a lower prevalence of plaque and NC/V-P, as well as differences in key immune/inflammatory biomarkers. Immune-plaque relationships differed by sex for D-dimer but not other tested parameters. Clinical Trial Registration. ClinicalTrials.gov; identifier: NCT0234429 (date of initial registration: 22 January 2015). Abstract : Among US persons with HIV (PWH), females demonstrated a lower prevalence of subclinical coronary artery disease (CAD), as well as differences in key immune/inflammatory biomarkers. Understanding sex-specific immune drivers of subclinical CAD will facilitate appropriately tailoring cardiovascular disease–preventive therapies to PWH.